2016
DOI: 10.1016/j.chemosphere.2016.06.102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of arsenate reduction and release by three As(V)-reducing bacteria isolated from arsenic-contaminated soil of Inner Mongolia, China

Abstract: h i g h l i g h t sWe isolated three anaerobic As(Ⅴ)-reducing bacterium from soil with high ratio of As(Ⅲ). Strains JQ, DJ-3 and DJ-4 could transform very high concentration of As(Ⅴ) to As(Ⅲ). All the three strains could release goethite-adsorbed As(Ⅴ) into solution. We compared the three strains with other previously isolated strains. The existence of the strains will cause the mobilization and transformation of As in soil. Handling Editor: X. Cao Keywords:As(Ⅴ)-reducing bacteria Arsenate reduction As release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Some other species of this genus have already been reported to resist As (Cai et al . ; Pandey and Bhatt ). The tolerance of As 5+ against E. profundum PT2 in LB and AWWE reported in this study is one of the highest As tolerance levels by any bacterial isolate reported previously (Kaur et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some other species of this genus have already been reported to resist As (Cai et al . ; Pandey and Bhatt ). The tolerance of As 5+ against E. profundum PT2 in LB and AWWE reported in this study is one of the highest As tolerance levels by any bacterial isolate reported previously (Kaur et al .…”
Section: Discussionmentioning
confidence: 99%
“…Then the mixture was stored at -20°C before PCR amplification. The 16S rRNA genes were amplified with 27F and 1492R [37]. Conditions of PCR amplification were as follows: 5 min at 95°C; then 30 cycles of 30 s at 95°C, 30 s at 55°C, and 90 s at 72°C; then 10 min at 72°C and a hold at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…DJ-3 and Exiguobacterium sp. DJ-4, were isolated from the soil of an arsenic-contaminated mine in Inner Mongolia, China . Strains DJ-3 and DJ-4 can utilize Fe­(III) and As­(V) as electron acceptors. , Among these strains, DJ-4 is the first Exiguobacterium strain isolated from soil that is capable of reducing As­(V) …”
Section: Introductionmentioning
confidence: 99%